Entrepreneurial Ecosystem for Fostering Women Entrepreneurship in Sri Lanka - Premaratna, S.P.; Hennayake, H.M.N.; Arachchi, P.S.K.; Premaratne, H. (Department of Economics, University of Colombo, Sri Lanka., 2025)
Women entrepreneurs are a vital yet underutilized driver of economic growth and social equity in Sri Lanka. Despite the pivotal role of small and medium enterprises (SMEs) in the national economy, women’s participation remains disproportionately low due to entrenched structural, institutional, and socio-cultural barriers. This study critically examines the entrepreneurial ecosystem (EE) in Sri Lanka through a gender lens, identifying systemic constraints that impede women’s entrepreneurial engagement and growth. Grounded in systems theory, feminist institutionalism, the resource-based view, and the capability approach, the paper develops a comprehensive analytical framework to assess the inclusivity of the current EE. This study integrates qualitative insights, stakeholder mapping, and quantitative data collected from a representative sample of 384 SMEs across Sri Lanka to identify critical gaps and formulate strategic interventions aimed at fostering a more gender responsive and equitable entrepreneurial ecosystem. The study finds that many of the issues related to SME development are towards the supply side. The findings contribute to the broader discourse on inclusive entrepreneurship and offer policy relevant recommendations for ecosystem reform in developing contexts.
Keywords: Entrepreneurial ecosystem; SMEs; Sri Lanka; Women entrepreneurship